THE ROLE OF TOP MANAGEMENT SUPPORT AND EFFECTIVE COMMUNICATION ON SUCCESSION PLANNING EFFECTIVENESS: AN EMPIRICAL STUDY OF OMANI CIVIL SERVICE ORGANIZATIONS - Al Jahwari A.; Alwi M.N.R. (LLC CPC Business Perspectives, 2024)
Succession planning is vital to protecting any organizations growth, development, and survival. While a good organizational strategy intends to ensure growth and strong management provides profitability, only an effective succession plan can make organizations sustainable. Top management support and effective communication are considered among the dominant factors that impact the effectiveness of succession planning. This study aims to investigate the impact of top management support and effective communication on the effectiveness of succession planning implementation in civil service organizations in the Sultanate of Oman. A survey was adopted based on the research objectives and administered to 160 employees from civil service organizations in Oman. Random purposive sampling was implemented due to its effectiveness in obtaining a representative sample for this study. Descriptive and inferential statistics, including mean, standard deviation, correlations, and regression analysis, were applied using SPSS software. The findings revealed that most participants considered the current succession planning and talent development practices ineffective in preparing talents for future needs in Oman. Moreover, the results demonstrated that effective communication has a positive and significant impact on succession planning effectiveness. Surprisingly, top management support and succession planning effectiveness are positive but insignificant. Finally, effective communication and support from top management through the succession planning stages are required to achieve the targeted objectives of the plans. Abdullah Al Jahwari, Mohd Nur Ruzainy Alwi, 2023.